Mechanism of siRNA production by a plant Dicer-RNA complex in dicing-competent conformation - Wang, Qian; Xue, Yan; Zhang, Laixing; Zhong, Zhenhui; Feng, Suhua; Wang, Changshi; Xiao, Lifan; Yang, Zhenlin; Harris, C. Jake; Wu, Zhe; Zhai, Jixian; Yang, Maojun; et al. (Science (American Association for the Advancement of Science), 2021)
In the biogenesis of small RNAs, the Dicer family endonucleases act as a molecular ruler to cut the substrate RNA into defined lengths. Wang et al . report a structure of the dicing-competent state of plant DICER LIKE PROTEIN 3 (DCL3) in complex with a pre–small interfering RNA (pre-siRNA). Toward one end of the pre-siRNA, DCL3 uses a positively charged pocket and an aromatic cap to specifically recognize the 5′-phosphorylated adenosine of the guide strand and the 3′ overhang of the complementary strand, respectively. On the other end, the paired ribonuclease III domains of DCL3 cut both strands of the RNA, determining the precise length of the product small RNA. —DJ Structural studies, complemented by functional data, elucidate the dicing principle for Dicer endonucleases in plants and more widely. In eukaryotes, small RNAs (sRNAs) play critical roles in multiple biological processes. Dicer endonucleases are a central part of sRNA biogenesis. In plants, DICER-LIKE PROTEIN 3 (DCL3) produces 24-nucleotide (nt) small interfering RNAs (siRNAs) that determine the specificity of the RNA-directed DNA methylation pathway. Here, we determined the structure of a DCL3–pre-siRNA complex in an active dicing-competent state. The 5′-phosphorylated A1 of the guide strand and the 1-nt 3′ overhang of the complementary strand are specifically recognized by a positively charged pocket and an aromatic cap, respectively. The 24-nt siRNA length dependence relies on the separation between the 5′-phosphorylated end of the guide RNA and dual cleavage sites formed by the paired ribonuclease III domains. These structural studies, complemented by functional data, provide insight into the dicing principle for Dicers in general.